1996
DOI: 10.1007/bf00048195
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase activity and isoenzymes in the culture medium of NaCl adapted tomato suspension cells

Abstract: The medium of tomato (Lycopersicon esculentum) cells adapted to grow in the presence of 15 g 1-1 NaC1 had a higher peroxidase activity than the medium of an unadapted tomato cell line. When the adapted cells were cultured in a medium without NaCI, the value found for peroxidase activity was intermediate. The increase in peroxidase activity was parallel to an increase of lignin-like compounds in the cell walls, as well as to an increased content or appearance of neutral and basic peroxidase isoenzymes. Apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 32 publications
1
26
1
1
Order By: Relevance
“…In plants, POD protects cells against harmful concentrations of hydroperoxides and helps in a variety of cellular functions (Beauchamp and Fridovich 1971). Increased total peroxidase activities in response to salinity were reported by Sancho et al (1996). A similar increase in POD was also observed after the application of Ni to the leaves of Silene italica (Gabbrielli et al 1987).…”
Section: Resultsmentioning
confidence: 85%
“…In plants, POD protects cells against harmful concentrations of hydroperoxides and helps in a variety of cellular functions (Beauchamp and Fridovich 1971). Increased total peroxidase activities in response to salinity were reported by Sancho et al (1996). A similar increase in POD was also observed after the application of Ni to the leaves of Silene italica (Gabbrielli et al 1987).…”
Section: Resultsmentioning
confidence: 85%
“…Anaerobic tissue has a very high redox potential and the soil environment surrounding the roots contains highly reduced forms of metal ions such as iron, which could readily reduce atmospheric oxygen to superoxide. 19 The levels of ascorbate peroxidase and glutathione reductase activity in cv. Pei at various NaCl concentrations are shown in Fig 2 At 150 mM NaCl, the activity of the two enzymes was increased.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that in the stress conditions of intense light, high temperature, flood and salinity, free radicals and reactive oxygen molecules are formed. 1,4,6,11,19 Therefore, a scavenging system should be active. Our results showed that cv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, POD protects cells against harmful concentrations of hydroperoxides and helps in a variety of cellular functions [37]. Increased total peroxidase activities in response to salinity were reported by [38]. A similar increase in POD was also observed after the application of Ni to the leaves of Silene italic [39].…”
Section: Superoxide Dismutase (Sod) Peroxidase (Pod) and Catalase Actmentioning
confidence: 48%